2021
DOI: 10.1101/2021.09.08.459390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of age and surface instability on the control of the center of mass

Abstract: During standing, posture can be controlled by accelerating the Center of Mass (CoM) through shifting the center of pressure (CoP) within the base of support by applying ankle moments ('CoP mechanism'), or through the 'counter-rotation mechanism', i.e., changing the angular momentum of segments around the CoM to change the direction of the ground reaction force. Postural control develops over the lifespan; at both the beginning and the end of the lifespan adequate postural control appears more challenging. In t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 49 publications
0
10
1
Order By: Relevance
“…We found that children used the counter-rotation mechanism relatively more to accelerate the CoM compared to younger adults. This is in contrast to our previous study using balance boards that could freely move in the frontal plane, in which we did not find an effect of age on the relative use of the counter-rotation mechanism (van den Bogaart et al, 2022). The increased contribution of the counter-rotation mechanism in children cannot be explained by differences in body height between children and younger adults, as accelerating the body center of mass by the counter-rotation mechanism is less efficient at lower height (A.1.1.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We found that children used the counter-rotation mechanism relatively more to accelerate the CoM compared to younger adults. This is in contrast to our previous study using balance boards that could freely move in the frontal plane, in which we did not find an effect of age on the relative use of the counter-rotation mechanism (van den Bogaart et al, 2022). The increased contribution of the counter-rotation mechanism in children cannot be explained by differences in body height between children and younger adults, as accelerating the body center of mass by the counter-rotation mechanism is less efficient at lower height (A.1.1.…”
Section: Discussioncontrasting
confidence: 99%
“…Decreased pertinence of proprioceptive information from ankle muscles and a reduction of the effectiveness of ankle moments to accelerate the CoM when standing on a balance board could be an explanation for this (Horak et al, 2001; van Dieen et al, 2015). The number of balance losses (23), with balance boards that could freely move in the sagittal plane, was much larger than in our previous study (van den Bogaart et al, 2022), with uniaxial balance boards that could freely move in the frontal plane (3). Surface instability in the sagittal plane thus seems more challenging compared to surface instability in the frontal plane.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations